A Robotic Arm based Prosthetic Food Feeding Mechanisms for Upper Limb Amputees - Logeswaran T, Elango S, Ramraj B, Prabhu M (International Journal of Advanced Science and Technology, 2020)
The objective of this work is to design and develop a robotic arm based feeding system to minimise the food wastage while feeding it to upper limb amputees. Assistive food feeding mechanism built with a robotic Arm available in the market is not efficient and economical to feed food and also it results in more wastage of food. To overcome this, we had designed a bowl pertaining to users need. The bowl is designed in such a way that it tilts to various positions, for example, when the amount of food in the bowl reduces to 30 percentage from its initial value, the bowl tilts about 0 degree to 35 degree. Prototype has been built with the combination of the robotic arm and tilted bowl design. Results of testing the model depicts that the level of food wastage is minimized while for feeding food to upper limb amputees. Keywords: Amputees, Upper limb, feeding device, robotic arm, food feeding, prosthetic device